Pengaruh Perubahan Dimensi Filter-Drier Dan Pipa Kapiler Terhadap Coefficient Of Performance (COP) Mesin Pendingin Kulkas 2 Pintu - Khairul Mustofa; Yohanes Primadiyono (Jurnal Teknologi Terapan, 2021)
COP on a cooling machine is used to reveal the performance of a cooling engine. To increase the COP value in the system, it can be done by changing the dimensions of the filter-drier and capillary pipes used. Therefore, this study was conducted to determine the effect of changing the dimensions of the filter-drier and capillary pipe on the COP and the consumption of electrical power produced by the 2-door refrigerator unit. The method used was an experimental method, namely by varying the filter drier and capillary tube dimensions of the 2-door refrigerator. Variations of filter driers used were filter driers with sizes 7 cm and 9 cm. While the capillary pipes used were 0.31 inches in diameter and 0.51 inches in diameter with a length of 200 cm and 250 cm respectively. The results obtained from this study indicate that the greatest COP value is obtained when using a 7 cm filter-drier and a capillary pipe with a diameter of 0.31 inches with a length of 200 cm, which is 2.80. The COP value also continues to decline as the size of the filter-drier and capillary pipes used increases.